Productivity and US macroeconomic performance: Interpreting the past and predicting the future with a two-sector real business cycle model - Peter N. Ireland; Scott Schuh (Federal Reserve Bank of Boston, 2006)
A two-sector real business cycle model, estimated with postwar U.S. data, identifies shocks to the levels and growth rates of total factor productivity in distinct consumption- and investmentgoods- producing technologies. This model attributes most of the productivity slowdown of the 1970s to the consumption-goods sector; it suggests that a slowdown in the investment-goods sector occurred later and was much less persistent. Against this broader backdrop, the model interprets the more recent episode of robust investment and investment-specific technological change during the 1990s largely as a catch-up in levels that is unlikely to persist or be repeated anytime soon.
Keywords: E32; O41; O47; 330; Real Business Cycle; Produktivität; Wirtschaftswachstum; Mehr-Sektoren-Modell; USA